2022
DOI: 10.3389/fphar.2021.762077
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Quality is Linked to Elevated Extracellular Vesicle-Associated Inflammatory Cytokines in Warfighters With Chronic Mild Traumatic Brain Injuries

Abstract: Background: Elevations of inflammatory cytokine levels occur immediately after mild traumatic brain injury (mTBI) and can persist for years. These elevations have been associated with neuropsychological outcomes, including depression and PTSD symptoms. Sleep disorders, another common sequelae of mTBI, are independently associated with inflammation in otherwise healthy individuals. However, whether sleep and inflammation are linked in chronic mTBI has not been reported.Methods: A retrospective cross-sectional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…These findings extend previous cross-sectional research by demonstrating that serum biomarkers associated with the presence of current neurobehavioral dysfunction (eg, postconcussion symptoms, depression, sleep problems, and cognition6–16) may also be associated with neurobehavioral functioning in the chronic phase of recovery. In addition, these findings extend previous longitudinal research by demonstrating an association between elevated serum tau and UCHL-1 within the first 12 months of injury, with the prediction of neurobehavioral status 2 or more years following a TBI.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings extend previous cross-sectional research by demonstrating that serum biomarkers associated with the presence of current neurobehavioral dysfunction (eg, postconcussion symptoms, depression, sleep problems, and cognition6–16) may also be associated with neurobehavioral functioning in the chronic phase of recovery. In addition, these findings extend previous longitudinal research by demonstrating an association between elevated serum tau and UCHL-1 within the first 12 months of injury, with the prediction of neurobehavioral status 2 or more years following a TBI.…”
Section: Discussionsupporting
confidence: 85%
“…T HE ROLE OF BLOOD-BASED biomarkers has received considerable attention in the literature as possible diagnostic and prognostic indicators following traumatic brain injury (TBI) in the acute and postacute period of recovery. To date, the majority of the literature is cross-sectional in design and has focused on establishing the association between protein biomarkers (such as serum tau, neurofilament light chain [NFL], glial fibrillary acidic protein [GFAP], and ubiquitin carboxyl-terminal hydrolase L1 [UCHL-1]) with the presence/absence of TBI, TBI severity, neuroimaging, mortality rates, and disability severity ratings following moderate to severe TBI, [1][2][3][4][5] in addition to more subtle neurobehavioral outcomes commonly associated with the sequelae of mild TBI (eg, postconcussion, anxiety, depression, sleep, and cognition [6][7][8][9][10][11][12][13][14][15][16] ). In other diseases, including cognitive impairments related to dementia, these same protein biomarkers show risk over time for cognitive declines, indicating that there may be a similar link within individuals following TBI.…”
mentioning
confidence: 99%
“…Indeed plasma-derived EVs from warfighters display increased levels of cytokines like IL-10, which positively correlated to poor sleep quality in TBI patients. 295 Thus, a detailed investigation is needed to delineate further the mechanisms involved in EV-mediated effects on neuroinflammation in TBI.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…It has been shown that the microglia undergo necroptosis in TBI, resulting in expanded patient inflammatory profiles. Though a direct correlation between EVs and the neuroinflammatory cascade in TBI is underexplored, a correlation is suggestive, given the immunomodulatory roles of EVs. Indeed plasma-derived EVs from warfighters display increased levels of cytokines like IL-10, which positively correlated to poor sleep quality in TBI patients . Thus, a detailed investigation is needed to delineate further the mechanisms involved in EV-mediated effects on neuroinflammation in TBI.…”
Section: Role Of Evs In Brain Disorders: Involvement In Pathogenesis ...mentioning
confidence: 99%
“…Furthermore, another study found that sleep can modify immune system functions by inducing changes in the hypothalamus-pituitary-adrenal axis and the sympathetic nervous system (63). In addition to the aforementioned studies based on non-TBI population, Gottshall et al also investigated the association between sleep quality and cytokines (IL-10, IL-6, and TNF-α) in the plasma and plasma-derived extracellular vesicles (EVs) in chronic mTBI (64). Same to the current study, they also found that plasma IL-6 was positively correlated with sleep quality; however, this association was absent in their study after adjusting for the effect of age, sex, and BMI.…”
Section: Sleep Disturbancesmentioning
confidence: 99%